Designing a smart learning environment based on (synchronous and asynchronous) e-learning and its impact on students’ acquisition of computer application skills - gazi, Osama; fayyadh, Etmad; mohammed, Ghada (Journal of Madenat Alelem University College, 2023)
The current research aims to design a smart learning environment based on the two types of e-learning (synchronous and asynchronous) and reveal its impact on students’ acquisition of computer application skills by verifying two hypotheses. The first states that (there is a statistically significant difference at the level of significance (0.05) between the average scores of the students of the first experimental group who study according to a smart learning environment based on synchronous electronic learning and the control group students who study according to a smart learning environment based on asynchronous e-learning in the theoretical computer applications test) The second states that (there is a statistically significant difference at the level of significance (0.05) between the average scores of the students of the first experimental group who study according to a smart learning environment based on synchronous e-learning and the students of the control group who study according to a smart learning environment based on asynchronous e-learning in the practical computer applications test) The research community has been chosen by the law department students at the University of Science. A semi-experimental design was employed with the experimental and control groups, and randomly, group (A) was chosen to be the first experimental group and group (B) to be the second experimental group, with (20) students for each group. A smart learning environment based on synchronous and asynchronous e-learning, preparing the necessary requirements, such as establishing an educational platform and providing various digital learning resources and teaching plans. A test was built to measure theoretical achievement, and a note card to measure practical achievement. The study experiment lasted twelve weeks and was conducted during the first semester of the academic year 2021–2022. After teaching the whole curriculum, the two groups completed an in-person theoretical and practical accomplishment exam. Students in the first experimental group did better on the theoretical and practical accomplishment exam than students in the second experimental group, according to statistical data analysis using the t-test for two independent samples. Keywords: Smart learning environment design, synchronous e-learning, asynchronous e-learning, computer applications.